2013
DOI: 10.5005/jp-journals-10006-1236
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Maternal Mortality: Our Scenario

Abstract: Objective: To analyze the cases of maternal mortality over a period of 3 years with regard to direct, indirect and associated causes and social correlates. Materials and methods:Retrospective evaluation of the cases with respect to causes, admission to mortality interval, age, parity, antenatal booking, socioeconomic status, etc. and systemic analysis of all contributing factors. Result and observation:A total of 66.67% of the deaths were due to direct causes with obstetric hemorrhage being the most common cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…12 The trend continues to 2008-2011, but the difference in mortality percentage between multigravidae (51%) and primigravida (42%) lessen. 13 And then, in the following studies and as in the present study there is a transition to increasing primigravida succumbing. 14 Higher order births have higher risk of pregnancy induced morbidities and are managed as high risk pregnancies in referral units.…”
Section: Discussionsupporting
confidence: 68%
“…12 The trend continues to 2008-2011, but the difference in mortality percentage between multigravidae (51%) and primigravida (42%) lessen. 13 And then, in the following studies and as in the present study there is a transition to increasing primigravida succumbing. 14 Higher order births have higher risk of pregnancy induced morbidities and are managed as high risk pregnancies in referral units.…”
Section: Discussionsupporting
confidence: 68%
“…Anaemia was found in 21 cases of maternal deaths. Studies done by Monica Soni et al 23 , Surat Zaman et al 21 , Jadhav CA 24 et al showed comparable results.…”
Section: Resultsmentioning
confidence: 70%
“…PPH also needs special attention because it can lead to death very rapidly in the absence of prompt life-saving care. 16 The time available for intervention being short, demands an efficient medical back-up for all deliveries. Institutional deliveries should be reached to 100%.…”
Section: Discussionmentioning
confidence: 99%